Association of trauma, posttraumatic stress disorder and conduct disorder: a systematic review and meta-analysis - Bernhard, Anka; Saure, Daniel (Neuroscience & biobehavioral reviews, 2018)
Objective - To summarize findings of previous studies on the prevalence of trauma and Posttraumatic Stress Disorder (PTSD) in Conduct Disorder (CD). - Method - We conducted a systematic review and meta-analysis following the PRISMA guidelines. EBSCOhost, PubMed, CDSR and ARIF databases were searched in October 2016, employing relevant keywords. - Results - 19 studies met inclusion criteria. Meta-analysis resulted in a lifetime PTSD prevalence of 11% (95% CI: 7–17%) in children and adolescents with CD, 14% (95% CI: 12–15%) in adults with pre-existing CD and 32% (95% CI: 25–40%) in juvenile offenders with CD. Higher lifetime PTSD prevalence was observed in individuals with than without CD, and in females compared to males with CD. - Conclusions - Studies focusing on the association of trauma, PTSD and CD are still relatively rare. Possible comorbidity models are discussed considering psychological and biological risk factors in a comprehensive model. The high rate of PTSD in CD may be due to shared risk factors; furthermore, CD might increase the risk for comorbid PTSD due to CD inherent risk taking behavior. To study pathways of risk, especially longitudinal studies are necessary.
Gesehen am 30.07.2019
Available online 23 December 2016